INFLUENCE OF ZINC FERTILIZATION ON MORPHO-PHYSIOLOGICAL ATTRIBUTES, GROWTH, PRODUCTIVITY AND HEMATIC APPRAISAL OF PADDY RICE - Q. U. Zaman; Z. Aslam; M. Rashid; A. Khaliq; M. Yaseen (Journal of Animal and Plant Sciences, 2018)
Zinc (Zn) deficiency is one of the main micronutrient disorders in rice and it may inflict its deficiency in the people feeding on it. Selection of rice genotypes with higher potential of Zn uptake is considered as natural and better way to combat malnutrition. Present study evaluated the potential of foliar and soil applied Zn in improving the performance of paddy rice and Zn bioavailability. In glass house, different sources of zinc (ZnSO .7H O and ZnCl ) and rate treatments 4 2 2 -1 -1 -1 -1 for soil (control, 5 kg ha , 10 kg ha , 15 kg ha and 20 kg ha of Zn) and foliar application ( control, 0.25%, 0.5%, 0.75% and 1% solution) were used. Selected rate and source treatments were appraised in field experiments. The rice grains -1 harvested thereof were fed to albino rats for Zn bioavailability. Results revealed that soil application with 15 kg ha and foliar application of 0.25% solution using ZnSO .7H O improved the early seedling growth of rice genotypes by 4 2 modulating the agronomic, water related and biochemical attributes. Field experiments confirmed that Zn application through soil and foliar spray improved the performance of rice genotypes by improving growth attributes, chlorophyll pigments, and yield and resulted in Zn enrichment of rice grains in various genotypes. The maximum weekly body weight gain and white blood cells count of albino rats was observed for feeding the kernels of Accession-164 ( high Zn) -1 as compared with the minimum for Super Basmati (low Zn) feed. In crux, soil application of ZnSO at 15 kg ha 4 followed by foliar application of 0.25% ZnSO solution at tillering and heading stage not only recorded the highest 4 growth and grain yield, but also showed maximum bioavailable Zn in the grains. Such rice grains with high Zn concentrations were also effective for combating malnutrition in the tested rats. Zinc is required for the synthesis of tryptophan
Keywords: Rice; Zinc; Growth; Seedling; Rats.